Экспериментальное исследование прочности многокомпонентного элемента защитной конструкции при растяжении и ударе - Хавин, Валерий Львович; Киркач, Борис Николаевич; Киркач, Алексей Борисович; Степук, Александр Владимирович (НТУ "ХПИ", 2017)
Представлены результаты комплексных испытаний на прочность одиночных элементов и пакетов элементов тонкостенной защитной конструкции. Путем испытаний на растяжение получены величины разрывных усилий для фрагментов защитной конструкции, состоящих из двух, трех и четырех последовательно соединенных элементов. Также проведены испытания одиночных элементов защитной конструкции на удар коническим стальным пробойником. На основе полученных экспериментальных данных произведена оценка степени разрушающего (проникающего) воздействия при ударе в зависимости от кинетической энергии пробойника, а также разрывной прочности замковых элементов соединений.

The results of an experimental strength study on single- and multi-element fragments of a multi-component thin-wall roller shutter protective structure are presented. In the framework of the study tensile tests were conducted to measure the in-plane rupture strength of the roller curtain using two-, three- and four-lath fragments of the structure. Also the impact tests on single-lath specimens of the roller shutter hit by a conical steel punch were performed. The results of the measurements were used to estimate the dependence of the kinetic puncher energy on the amount of impact penetration as well as the per unit length lock rupture force of the roller structure. The results obtained should contribute to the enhanced design and reliability of such protective structures as well as objects equipped with them.
Experimental study of strength of a multi-component protective structure element under tensile and impact loadings
Keywords: прочность на разрыв; разрушение; ударное воздействие; тонкостенный элемент; roller shutter structure; tensile strength; rupture